Potencial de bactérias do Rio Madeira na produção de biopolímeros - Ferreira, Edilane Martins (2015)
Plastics play a fundamental role in society, with different purposes and broad market, constantly growing. Major environmental problems occur due to excessive use of petroleum-derived plastics, mainly due to its rapid disposability and slow degradation, affecting life quality of the current population, resulting in the need to find alternatives to replace this material. Biodegradable plastics are presented as solution, which are polymers with desirable properties of conventional plastics and quickly biodegradability when discarded into the environment. Among them there are polyhydroxyalkanoates (PHAs), a large family of polyesters, intracellulars, accumulated in the form of granules by various bacteria from renewable sources substrates, using it as carbon and/or energy source, under limitation of an essential nutrient for their growth. The objective of this study is to select bacteria capable of producing PHA, from the collection of microorganisms of the “Laboratório de Microbiologia do Mestrado em Biotecnologia e Recursos Naturais da Universidade do Estado do Amazonas –MBT/UEA”. Initially, 140 isolates sampled from Madeira River of Autazes municipality (Amazonas State) in 2010, were reactivated and purified through NA and MM. To select bacteria lines with biopolymer production potential, all isolates were stained with Sudan Black, and 47 were positive for staining. Within the positive group, 08 isolates were selected for presenting major cell morphological changes when seen in the microscope, suggesting potential for biopolymers production. Then they were stained with Nile Red and Nile Blue to confirm biopolymer production. To elucidate qualitatively and quantitatively the PHAs produced by the 08 isolates, it was used the lyophilized cellular mass performing methanolysis for biopolymer extraction. Thus, samples were analyzed by gas chromatography. As result, from 08 isolates identified by partial sequence identity of 16S rRNA, there were species belonging to three genera: Bacillus, Brevibacterium and Lynisibacillus, being genus Bacillus the most significant, thus having desirable characteristics for PHA production, such as short generation time, easy growth until reaching a high cell density and use of low cost carbon and nitrogen source. All identified isolates are gram-positive, providing the advantage of the lack of LPS and protein excretion, which make them good candidates as PHA producers for biomedical applications. Chromatographic analysis revealed a polymer consisting mainly of monomer 3-hydroxybutyrate (HB). It is noteworthy that on Brevibacterium genus there are very few published studies about the production of biopolymers and in terms of gender Lysinibacillus did not report anything about the production of biopolymers, yet. These results demonstrate the importance of bio prospection works aiming to detect bacteria PHA producers. . Keywords: Biopolymers, Polyhydroxyalkanoates, Madeira River, Bacillus sp., polyhydroxybutyrate.